Development and Integration of a CO Detection System Based on Wavelength Modulation Spectroscopy Using Near-Infrared DFB Laser - Bin Li; Shuo-Cheng Zhang; Yao-Dan Chi (Journal of Spectroscopy)
A wavelength modulation spectroscopy- (WMS-) based gas sensing system was established to measure concentration of carbon monoxide (CO) in the range 0–100%. The CO absorption line at 1563.06 nm was scanned with a tunable distributed feedback (DFB) laser, and two InGaAs photodiodes were applied to perform optic-electric conversion. Without using commercial instruments, essential electrical circuits were self-developed and integrated, including laser temperature controller, laser current driver, signal generator, and digital lock-in amplifier. The gas cell deployed in the system was fiber coupled with a total effective optical path length of 50 cm. The second-order harmonic signal was extracted, and experiments of gas detection were carried out to investigate the performance of the sensor, including detection repeatability, detection accuracy, response time, and limit of detection (LoD). Experiment results show that the sensor is reliable and has acceptable probing performance. The maximum relative detection error is less than 3.8%, suggesting good detection stability. Benefiting from the self-developed sensor, the whole CO detection system has small size, affordable expense, and application potential.